In-Silico Study Of Bone Cancer Activity Of Indole 3-Carbinol - .Periyasamy, S.K; Chozhan, C. Karikal; Rajeshkannan, R.; Muralidharan, K. (Journal of Neonatal Surgery, 2025)
This study aims to describe the bone cancer activity of Indole-3- carbinol. This compound is predicted as a potential drug in medicinal field confirmed by Swiss ADME software. Further, the bone cancer activity of Indole-3-carbinol was analyzed by Auto docking study and found out the binding energy of compound which confirms that this can be a potential bone cancer drug. Hence, Indole – 3 carbinol is expected to be an effective bone cancer drug in medicinal field as well as in the society.